1996
DOI: 10.1093/hmg/5.7.981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three mutations and associated haplotypes in the protoporphyrinogen oxidase gene in South African families with variegate porphyria

Abstract: Mutation analysis of genomic DNA samples obtained from 17 unrelated South African patients with variegate porphyria (VP) revealed three novel missense mutations in the protoporphyrinogen oxidase (PPOX) gene. A common C to T transition at nucleotide position 452 (R59W) was identified in 15 of the patients analysed, while base changes at positions 336 (H20P) and 779 (R168C) were identified in the remaining two patients. Using protein analysis software we were able to predict that all three mutations have a simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 11 publications
3
77
0
Order By: Relevance
“…Identification of the cDNA for PPOX (18 ) and recognition that the founder R59W mutation accounts for 95% of all South African patients with VP (19,20 ) have enabled the assignment of an accurate genotypic diagnosis in our patients and has in turn allowed us to determine accurately the sensitivity and specificity of biochemical testing in our population. Our findings are reported here.…”
mentioning
confidence: 99%
“…Identification of the cDNA for PPOX (18 ) and recognition that the founder R59W mutation accounts for 95% of all South African patients with VP (19,20 ) have enabled the assignment of an accurate genotypic diagnosis in our patients and has in turn allowed us to determine accurately the sensitivity and specificity of biochemical testing in our population. Our findings are reported here.…”
mentioning
confidence: 99%
“…Although in more recent years some admixture has occurred, the population growth over 13-15 generations was almost entirely through reproduction, as immigration subsequent to the founding was minimal. The demographic history of this population is reflected in the unusually high frequency of certain rare Mendelian disorders, the unusually low diversity of the associated allelic variants, and the unusually large extent (8-11 cM) of conserved haplotypes around disease genes (Hayden et al 1980;Brink et al 1987;Rosendorff et al 1987;Leitersdorf et al 1989;Torrington and Viljoen 1991;Brink et al 1995;Pronk et al 1995;Goldman et al 1996;Warnich et al 1996;Groenewald et al 1998;Roby et al 1999).…”
mentioning
confidence: 99%
“…Crystal Structure of R59Q and R59G Mutant-The R59W mutation is by far the most prevalent VP-causing mutation identified, and Ͼ94% of the patients in South Africa carry this mutation (16,17). Biochemical studied showed that the R59W mutation dramatically decreased the catalytic constant of hPPO in vitro (17,21,41,42).…”
Section: Resultsmentioning
confidence: 99%
“…VP is a type of acute hepaticporphyria (9 -11), which is characterized by an abnormal pattern of porphyrin excretion. VP has been found worldwide (12)(13)(14)(15) and is particularly prevalent in the white population of South Africa (ϳ3 in 1000), especially VP caused by the R59W founder mutation (16,17).…”
mentioning
confidence: 99%